Gold mining in Ghana's forest reserves: A report on the current debate - Hilson, G.; Nyame, F. (Area, 2006)
This paper examines the debate surrounding a recent decision made by the Ghanaian government to permit gold exploration - and potentially, mining - in 'protected' forest reserves. In 2001, four mining companies were awarded mineral exploration concessions in forested regions of the country, and have since put forward applications to mine for gold. Notwithstanding the sharp divide in opinion on the issue, the continued uncertainty surrounding the implications of the proposed activities makes further research on the ground imperative in the short term. Work aiming to elicit indigenous perspectives on the projects, as well as research that facilitates dialogue between and/or among stakeholder parties, should be prioritized. © The Authors. Journal compilation © Royal Geographical Society (with The Institute of British Geographers) 2006.
Keywords: Community; Environmental; Forest reserves; Ghana; Gold mining